Avaliação da eficácia da prednisona na neurite hansênica aguda - ARAÚJO FILHA, Terezinha de Jesus Carvalho (Universidade Federal do Pará, 2013)
One of the biggest problems about leprosy is the development of acute neuritis, which may cause pain, impairment of neural functions and physical impairment. In spite of prednisone be the most used drug in the treatment of leprosy neuritis, its real efficacy rate is controversial and highly variable among different studies. The main objective of this work is to evaluate leprosy neuritis during the prednisone use, through neuroclinical examinations. The study was done in Dr Marcello Candia Reference Unit in Sanitary Dermatology of the State of Para´ (UREMC), with the inclusion of 23 patients (65% male gender) which were, in average, 40,5 years old. All had multibacillary leprosy, 20 were borderline and 3 lepromatous. Sixty-one percent of the patients had already been discharged from multidrug therapy. There were included in the study individuals who presented acute neuritis, associated with motor or sensitive function loss, using prednisone as proposed by the Brazilian Ministry of Health, with a 60 mg per day as initial dosage, followed by 5 to 10mg regression each 15 days. Clinical examination was done on the main peripheral nerves affected by leprosy. After 18 weeks follow-up, 60,87% of the patients needed prednisone for a longer time than initially proposed. Pain had a better clinical evolution than muscular strength and skin sensibility. There was pain relief in 71,23% of the nerves (p < 0,05), but 42,47% of the patients still had neuritis; there was improvement on the sensitive functions in 63,16% (p > 0,05), and on the motor function in 50% (p < 0,05) of the nerves. The results show that 18 weeks of prednisone use were not enough to resolve leprosy neuritis and the impairment of the neural functions in the majority of patients in this study.